Freshwater Slugs in the Caribbean: Rediscovery of Tantulidae (Acochlidimorpha, Panpulmonata) with the Description of Potamohedyle espinosai n. gen. n. sp. from Cuba - Timea P. Neusser; Anabel Onay; Mona Pirchtner; Katharina M. Jörger; Yander L. Diez (Hydrobiology)
Freshwater slugs are scarce and belong exclusively to panpulmonate Acochlidimorpha. There is a radiation of eight species of large-sized slugs living benthically in rivers on tropical Indo-Pacific Islands. In the Western Atlantic, only one small interstitial slug, Tantulum elegans Rankin, 1979, is known from the Caribbean island of St. Vincent. We recently discovered a novel species of freshwater slugs in Cuba. Here, we describe Potamohedyle espinosai n. gen. n. sp., which is the first freshwater slug in the region of the Western Atlantic with a benthic lifestyle, in 3D-microanatomical and histological detail using light and scanning electron microscopy. It shows a mix of characters from different freshwater acochlidimorph genera, such as a medium body size, the presence of an osphradial ganglion, a distal gonoduct with a muscular sphincter, a penis with a solid thorn and cuticular comb, and a basal finger with a hollow stylet. Morphological adaptations to a life in freshwater include multiplicated renopericardioducts. The taxonomic character mix justifies the establishment of a novel genus within the herein diagnostically modified freshwater family Tantulidae. A molecular phylogenetic hypothesis of riverine slugs including the first Caribbean representatives suggests that the transition to freshwater occurred once along the stemline of limnic Acochlidiidae, secondarily marine Pseudunelidae and limnic Tantulidae.